2021
DOI: 10.3389/fonc.2021.630260
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Prognostic m6A-Related lncRNA Signature in Gastric Cancer

Abstract: N6-methyladenosine (m6A) is a common form of mRNA modification regulated by m6A RNA methylation regulators and play an important role in the progression of gastric cancer (GC). However, the prognostic role of m6A-related lncRNA in gastric cancer has not been fully explored. This study aims at exploring the biological function and prognostic roles of the m6A-related lncRNA signature in gastric cancer. A total of 800 m6A-related lncRNAs were identified through Pearson correlation analysis between m6A regulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 24 publications
0
57
0
Order By: Relevance
“…Jin et al construct an m6A-related signature which could predict the response to immunotherapy in adrenocortical carcinoma (37). Wang et al constructed an m6Arelated lncRNA signature which could discriminate patients with response to immune checkpoint inhibitor in gastric cancer (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin et al construct an m6A-related signature which could predict the response to immunotherapy in adrenocortical carcinoma (37). Wang et al constructed an m6Arelated lncRNA signature which could discriminate patients with response to immune checkpoint inhibitor in gastric cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome profiling data and corresponding clinical data were downloaded from The Cancer Genome Atlas (TCGA) database (https://portal.gdc.cancer.gov). A list of 23 m6A regulators was obtained from a published article, which include writers (METTL3, METTL14, METTL16, WTAP, VIRMA, RBM15, RBM15B, and ZC3H13), erasers (FTO and ALKBH5), and readers (YTHDC1, YTHDC2, IGF2BP1, IGF2BP2, IGF2BP3, YTHDF1, YTHDF2, YTHDF3, HNRNPC, LRPPRC, HNRNPA2B1, FMR1, and RBMX) (24,28,29). The differential analysis of m6A regulators and m6A genes was obtained using "limma" package in R software.…”
Section: Data Source and Retrievementioning
confidence: 99%
“…However, more studies are needed to decipher the diversity of abnormal methylation or recognition abnormality of methylation position and tumor immunophenotype. Determining the role of various m 6 A modification modes in ccRCC microenvironment could improve our understanding of anti-tumor immune response and lay the foundation for personalized treatment of ccRCC patients ( 45 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that these regulators were mutated in LUAD, although the alteration frequencies were not high (Figure 6A, less than 4%). M6A modifications of lncRNAs were also demonstrated as the powerful evidences in cancer researches (31,32). Studies also found that m6A regulators could trigger lncRNA expression.…”
Section: Identification Of Lncrna-tf Positive Feedback Loopsmentioning
confidence: 94%